Long-Term Outcome of Vagus Nerve Stimulation for Drug-Resistant Epilepsy - Anuja Patil; Sita Jayalakshmi; Shanmukhi Somayajula; Dhrumil Shah; Sudhindra Vooturi; Manas Panigrahi (Annals of Indian Academy of Neurology)
Background and Objectives: In this study, we aimed to assess the long-term outcome of vagus nerve stimulation (VNS) in patients with drug-resistant epilepsy (DRE). Methods: A retrospective analysis of outcome data of 24 patients with DRE, who had been implanted with VNS and had at least 5 years of post-surgery follow-up was performed. The seizure outcome at the latest follow-up was classified as class I–V as proposed by John C. McHugh. The cognitive, psychiatric, and behavioral outcomes were recorded using standardized tests. Results: Mean age at the time of VNS implantation was 18.7 (6–38) years; nine (37.5%) of the patients were females. Mean duration of epilepsy was 13.6 years (range: 2.5–35 years); 18 (75%) patients had multiple (≥2) seizure types and 15 (62.5%) had daily seizures. The most common etiology was perinatal hypoxic injury (15, 62.5%). More than 50% seizure reduction (class 1 and 2) was noted in 54.2% of patients at 1 year, which increased to 75% at ≥5 years follow-up. A significantly higher number of patients with other etiologies had >50% reduction in seizures at the latest follow-up, when compared to those with hypoxic–ischemic encephalopathy (53.3% vs. 100%, P = 0.0024). The average intelligence quotient (IQ; 71.17 ± 28.92 vs. 64.65 ± 29.61, P = 0.014) and quality of life (66.64 ± 14.63 vs. 64.65 ± 29.61, P < 0.001) scores were significantly higher in patients post-VNS implantation, when compared to their baseline scores. Furthermore, significant number of patients had improvement in psychiatric diagnosis (29.2% vs. 4.2%, P = 0.047) and behavioral problems (50% vs. 4.2%, P < 0.001) post-VNS implantation. Conclusions: The present study shows >50% seizure reduction in 75% of patients after VNS implantation at long-term follow-up, with improvement in IQ, quality of life, psychiatric and behavioral problems.